Objective assessment of trismus in oral and oropharyngeal cancer patients treated with intensity-modulated radiation therapy (IMRT). Issue 9 (September 2016) - Owosho, Adepitan A.; Pedreira Ramalho, Luciana M.; Rosenberg, Haley I.; Yom, SaeHee K.; Drill, Esther; Riedel, Elyn; Tsai, C. Jillian; Lee, Nancy Y.; Huryn, Joseph M.; Estilo, Cherry L.
Abstract: Purpose: The aim of this study was to estimate the prevalence of trismus in oral and oropharyngeal cancer patients (OOPC) treated with intensity-modulated radiation therapy (IMRT) and to identify the role of risk factors in patients who developed trismus. Materials and methods: A retrospective cohort study of OOPC treated with IMRT in our institution from 2009 to 2014 was performed. Patients eligible for this study had pre-RT and post-RT maximal inter-incisal opening (MIO) measurements at 6–48 months post-RT, treated with high-dose radiation (≥60 Gy) and pre-RT MIO ≥36 mm. A descriptive analysis to identify the incidence of trismus, with trismus stated as MIO ≤35 mm at or after 6 months post-RT measurement was performed. The role of risk factors such as age, gender, tumor site, tumor size (T), tumor stage, pre-RT MIO measurements and radiation dose to the tumor were assessed using Fisher exact test and the radiation doses to the ipsilateral muscles of mastication in patients who developed trismus were assessed by matching with control (non-trismus) patients using Wilcoxon Signed Rank test. Results: The study consisted of 54 patients with a median age of 55 years and 81% were males. The median follow-up time was 10 months. The prevalence of trismus was 14.8%. Patients with pre-RT MIO measurements ≤40 mm were at risk of developing trismus ( P < 0.001). In trismus patients, the average mean radiation dose to the masseter and medial pterygoid muscles was numerically higher but not significantly different ( P = 0.08; P = 0.22, respectively) to matched control patients. Age, gender, radiation dose to the tumor, tumor site, size (T) and stage were also found to be not significant. Conclusion: Pre-RT MIO measurement was a significant risk factor for the development of trismus. However, this is a non-modifiable factor. Limiting radiation dose to the muscles of mastication could prevent this complication.